2010
DOI: 10.1007/s11240-010-9848-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome survey and characterization of MADS-box gene family in maize and sorghum

Abstract: MADS-box genes comprise a large gene family, which codes for transcription factors, and play important functions in various aspects of flowering plant growth and development. However, little is known about the MADS-box genes in maize (Zea mays) and sorghum (Sorghum bicolor). Here, we performed a comprehensive bioinformatics analysis of the MADS-box gene family in the maize and sorghum genomes and identified 75 maize and 65 sorghum MADS-box genes. We subsequently carried out a comparative analysis of these gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 57 publications
(67 reference statements)
7
56
0
Order By: Relevance
“…Although different MIKC-type genes have been isolated from several grass species (Bommert et al 2005;Whipple and Schmidt 2006;Dwivedi et al 2008), the most comprehensive cloning and characterization of genes encoding MADS-box transcription factors have been carried out in rice, maize, and sorghum (Munster et al 2002;Lee et al 2003a;Arora et al 2007;Zhao et al 2010), thanks to the completion of their whole-genome sequencing, and in wheat, wherein Paolacci et al (2007) carried out an extensive screening for MIKC-type cDNAs.…”
Section: Mikc-type Genes Of the Mads-box Family In Grassesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although different MIKC-type genes have been isolated from several grass species (Bommert et al 2005;Whipple and Schmidt 2006;Dwivedi et al 2008), the most comprehensive cloning and characterization of genes encoding MADS-box transcription factors have been carried out in rice, maize, and sorghum (Munster et al 2002;Lee et al 2003a;Arora et al 2007;Zhao et al 2010), thanks to the completion of their whole-genome sequencing, and in wheat, wherein Paolacci et al (2007) carried out an extensive screening for MIKC-type cDNAs.…”
Section: Mikc-type Genes Of the Mads-box Family In Grassesmentioning
confidence: 99%
“…The evolutionary relationships between MIKC-type genes of grasses and Arabidopsis were assessed through phylogenetic reconstruction based on the alignment of 134 amino acid sequences deduced from the nucleotide sequences of 34 genes of Arabidopsis (Parenicova et al 2003), 31 of rice (Lee et al 2003a;Arora et al 2007), 40 of maize (Munster et al 2002;Zhao et al 2010), and 29 of wheat (Paolacci et al 2007) (Fig. 4).…”
Section: Mikc-type Genes Of the Mads-box Family In Grassesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances in whole-genome sequencing have enabled genome-wide analyses of the MADS-box gene family in economically important crops, such as in grapevine (Diaz-Riquelme et al, 2009), maize, sorghum (Zhao et al, 2011), cucumber (Hu and Liu, 2012), and soybean (Shu et al, 2013). The Arabidopsis, grapevine, and cucumber genomes contained 39, 38, and 30 MIKCtype MADS-box genes, respectively (Diaz-Riquelme et al, 2009;Hu and Liu, 2012;Par̆enicová et al, 2003).…”
Section: -Type Mads-box Genes In E Grandiflorummentioning
confidence: 99%
“…Experiments on a variety of plant species have shown that inductive photoperiods cause leaves to emit a mobile signal termed 'florigen', which is a FT protein that travels from the vasculature to its site of action on the flanks of the shoot apical meristem (SAM). The FT protein acts at the shoot apex of the plant in concert with a transcription factor, FLOWERING LOCUS D (FD), to up-regulate expression of some MADSbox genes, such as AP1, a floral meristem identity gene and SOC1, a flowering-timing gene, and then induce the floral transition and initiation (Corbesier et al 2007;Jaeger and Wigge 2007;Mathieu et al 2007;Yang et al 2007;Zhao et al 2011).…”
Section: Introductionmentioning
confidence: 99%